Oligonucleotide-conjugated Nanomaterials as Biosensing Platforms to Potential Bioterrorism Tools - Frias, Isaac A.M.; da Silva Junior, Alberto G.; Oliveira, Maria D.L.; Andrade, César A.S. (Current Analytical Chemistry, 2023)
Availing diseases as warfare began before humans learned that microorganisms are involved in the dissemination of infections. In the past, war brigades had the intention to weaken rival groups by using festering corpses with the premeditated purpose of causing disease. Nowadays, the unfortunate improvement of biowarfare is indubitably linked to our extensive collaborative work in exploring the use of microorganisms and their derivatives to create products and services that are beneficial to society. Natural defense barriers such as innate immunity and the immune specific adaptive response come to mind when thinking of bacteria and virus potentially being operated as tools for biological warfare. On the other hand, some bacterial toxins disrupt the immune cell functions and others do not trigger sufficient immune response, thus being not suitable for immunotherapy applications. As an alternative to these drawbacks, the systematic evolution of ligands by exponential enrichment (SELEX) develops specific nucleic acid or peptides for a variety of targets, including toxins. These aptamers are efficiently produced in vitro using enzymes or synthetical synthesis within days, low cost, and reproducibility. Oligonucleotide aptamers are a nanotechnological high spot because of their physicochemical characteristics such as resilience, pH responsiveness, and addressability at the nanoscale. Additionally, they induce no immunogenicity and can be modified by association with nanoparticles to increase their stability in biological environments. In this review, we explore the recent trends and perspectives on biosensor construction based on oligonucleotide aptamer-conjugated nanomaterials as effective biosecurity devices and their relevance to the development of risk-assessment protocols that could be used as intelligent barriers to provide continuous, cheap, and easy monitoring to prevent unexpected attacks.
Keywords: virulent factors